Projeto Sempre Sorrindo: 10 anos de atenção ao idoso institucionalizado - Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Silva, Milene Moreira [UNESP]; Joaquim, Renata Colturato [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2011)
Introduction: To correctly attend the health needs of the elderly population, it is necessary to invest in training of human resources. Thus, it becomes indispensable to insert the geriatric dentistry content into graduation courses. Objective: To describe the experiences and the results obtained during 10 years of an university extension project focused on oral health care of institutionalized elderly. Methodology: This is a documental and descriptive work, which was analyzed the institutional process of ten years of the University Extension Program, “Always Smiling - Dental Care for the Elderly Institutionalized of Araçatuba, “ developed at the Araçatuba Dental School, FOA/ UNESP. It were collected quantitative and qualitative data, and these were classified and interpreted according to the technique of categorizing the content. Results: In ten years of implementation, the project “Always Smiling” involved undergraduate students, professors and post-graduate students, who together have developed practical activities such as health education, hygiene supervision, recreational and educational activities, epidemiological surveys of oral health conditions and consequently, dental care according to the need of the treatment. Conclusion: The project “Always Smiling” serves as a working model for elderly health care, because it acts involves many aspects, from the prevention of diseases, even to the training of elderly caregivers, benefiting the institutionalized elderly and health professionals.

Introdução: Para atender adequadamente às necessidades de saúde da população idosa, é preciso investir na capacitação de recursos humanos. Desse modo, torna-se imprescindível integrar aos cursos de graduação o conteúdo de odontogeriatria. Objetivo: Descrever as experiências e os resultados obtidos em dez anos de um projeto de extensão universitária voltado para a atenção à saúde bucal do idoso institucionalizado. Metodologia: Trata-se de um trabalho documental, descritivo, no qual foi analisado o processo institucional de dez anos do Projeto de Extensão Universitária, “Sempre Sorrindo – Atenção Odontológica a Idosos Institucionalizados do Município de Araçatuba”, desenvolvido pela Faculdade de Odontologia de Araçatuba-UNESP. Foram coletados dados quantitativos e qualitativos. Estes últimos foram classificados e interpretados de acordo com a técnica de categorização de conteúdo. Resultados: Em dez anos de execução, o projeto “Sempre Sorrindo” envolveu alunos de graduação, professores e pósgraduandos que, juntos, desenvolveram atividades práticas como educação em saúde, supervisão de higienização, atividades lúdico-educativas, levantamentos epidemiológicos das condições de saúde bucal e, consequentemente, atenção odontológica de acordo com a necessidade de tratamento. Conclusão: O projeto “Sempre Sorrindo” serve como modelo de trabalho voltado à atenção à saúde do idoso, pois atua em amplos aspectos, desde a prevenção de doenças, até a capacitação de cuidadores de idosos, beneficiando, assim, internos e profissionais da saúde.
Always Smiling project: 10 years of attention for institutionalized elderly
Keywords: Geriatric dentistry; Public health; Aging; Odontogeriatria; Saúde Pública; Envelhecimento